SAT0034 WISP1 Aggravates Osteoarthritis by Modulation of TGF-β Signaling and Positive Regulation of Canonical WNT Signaling. (9th June 2015) - van den Bosch, M.; Blom, A.; Maeda, A.; Kilts, T.; van den Berg, W.; Lafeber, F.; van Lent, P.; Young, M.; van der Kraan, P.
Abstract : Background: Many osteoarthritis (OA) patients show synovial activation, which is suggested to be involved in joint destruction. Previously, we found strong upregulation of Wnts 2b and 16 in the synovium of two experimental OA models. In addition, we found increased expression of WISP1, a downstream protein of canonical Wnt signaling, in both synovium and cartilage. Objectives: To determine the role of WISP1 during OA by inducing experimental OA models in WISP1-deficient mice and to determine if WISP1 was involved in the progression of early OA in humans. Methods: Pathway analysis of microarray data from the synovium of a collagenase-induced OA (CIOA) and destabilization of the medial meniscus (DMM) model was performed using DAVID. Microarray analysis was performed on synovial tissue of patients with early complaints of knee or hip pain, enrolled in the CHECK study. Expression data was correlated with damage at baseline and progression between baseline and the five-year follow-up measurement. Progression was defined as decreased joint space width of at least 1 mm and progression of osteophyte formation of at least 4x in size. Experimental OA was induced in WT and WISP1 knockout mice. Joint pathology was assessed by histology. Human OA synovium was obtained after joint replacement surgery and stimulated with WISP1. Smad phosphorylation and β-catenin accumulation were determined using immunohistochemistry. Results: Pathway analysis showed enrichment of Wnt signaling in both the CIOA and DMM at various time points. In addition, microarray analysis of synovial tissue from patients in the CHECK study showed a correlation between WISP1 expression and damage at baseline. Moreover, WISP1 expression was correlated with the progression of OA between baseline and the five-year follow-up measurement. To further pinpoint the role of WISP1 in the etiopathology of OA, we induced experimental OA in WT and WISP1 KO mice. We found significantly decreased cartilage damage in the tibio-femoral joints of the WISP1 KO mice. Synovium of WISP1 KO mice showed reduced expression of MMPs, which is in line with our finding that stimulation of human OA synovium with WISP1 increased the MMP expression. TGF-β signaling via Smad 2/3 is crucial for maintaining cartilage homeostasis, while signaling via Smad 1/5/8 is associated with chondrocyte hypertrophy. To determine if WISP1 affects TGF-β signaling, we stained WT and WISP1 depleted joints for phosphorylated Smad 2/3 and found increased pSmad 2/3 in the WISP1 KO mice. In addition, recent data showed that WISP1 could regulate the accumulation of β-catenin, and positively control canonical Wnt signaling, further aggravating the OA pathology. Staining for β-catenin indeed showed that WISP1 depleted joints have decreased levels of β-catenin accumulation in the cartilage. Conclusions: Overexpression of WISP1 in the joint may play an important role in OA pathology via modulation of TGF-β signaling and positive feedback on canonical Wnt signaling. Targeting upstream Wnt signaling likely causes undesired side effects, as the pathway is extremely complex and involved in many processes. Specific downregulation of WISP1 may more specifically target pathological events that take place during OA without interfering with normal processes. Disclosure of Interest: None declared